RANCANG BANGUN UI/UX APLIKASI E-COMMERCE BERBASIS FRAMEWORK CODEIGNITER MENGGUNAKAN MODEL LEAN USER EXPERIENCE - Tukino, Tukino (Computer Based Information System Journal, 2024)
In today's era, some people require more specialized marketplaces for selling items such as driving equipment or automotive-related products. Individuals need consignment services to sell their driving gear like helmets, driving jackets, and other related items. Many people face difficulties in finding suitable and secure storage spaces for their belongings. This study explores the rapid expansion of internet usage, which has spurred the emergence of new business models, notably online marketplaces for buying and selling goods. The research focuses on developing a simple yet effective online store platform, particularly tailored for sellers at the Indonesian Helmet Shop. Employing the prototype method, this research constructs the application through various modeling techniques including use case diagrams, class diagrams, activity diagrams, and sequence diagrams. The primary objective is to create a lightweight, web-based marketplace application that enhances the transaction process between consignment providers and consumers. Preliminary findings suggest that the application facilitates efficient user interactions and transactions. However, further development is required in the areas of user interface (UI) and user experience (UX) to ensure greater consumer satisfaction and engagement. This study underscores the potential of tailored digital solutions in optimizing e-commerce platforms, particularly in specialized market sectors.